Evaluating the electronic data interchange adoption decision among Malaysian manufacturing companies / Lee Sai Leong - Lee, Sai Leong (2012)
Electronic Data Interchange has been in use from the early 1960s and has evolved over the last 50 years to include Internet EDI. Even though EDI has a long history, it is still very much in use today by major US and European automotive industry and the energy, healthcare, retail and manufacturing sectors. This is in spite of competing options from electronic procurement to enterprise resource systems. The main reason for its longevity is because it’s standards-based and its reliability has been proven through many years of commercial use. EDI has many benefits to offer its adopters. Notwithstanding this, businesses which adopt EDI has other imperatives to base their decisions. EDI has diffused from its early days in the United States, Europe and Japan to other parts of the world including South East Asia. Businesses which have to succeed in today’s competitive world have to resort to technology to improve their supply chain management. One of the dominant technologies which these businesses have to consider today is electronic data interchange. Electronic Data Interchange (EDI) has been used mainly in the shipping and logistics industry in Malaysia through the mandatory government initiated SMK-Dagang*Net for over a decade. In the non-mandatory category, EDI has been adopted by banks in Malaysia, the bigger Malaysian-based retailers as well as manufacturers in Malaysia. Until today EDI is still not widely diffused to other businesses in Malaysia. This study is exploratory in nature and has two major objectives. The first objective is to determine the function, diversity and breadth of EDI usage in Malaysian manufacturing companies. The second objective is to identify the significant factors that influence EDI adoption decisions. The motivation for the first objective is that there is a lack of current information on EDI use in manufacturing companies. The motivation for the second objective is to provide insight into why companies adopt or do not adopt electronic data interchange. The sampling frame was from the Federation of Malaysian Manufacturer’s (FMM) Directory. The usable sample of 284 companies consists of 86 (30.20%) EDI adopters and 198 (69.80%) EDI non-adopters. Manufacturers in Malaysia use EDI mainly for sales and purchase order transactions. This study found that the Internet is by far the most popular communications channel followed by private (VANs) and proprietary networks. The theoretical bases of diffusion of innovation (DOI) theory, social exchange theory (SET), trust theory and critical mass theory (CMT) have been synthesized into the Tornatzky and Fleischer’s (1990) technology-organization-environment research framework which was used for this study. Fourteen research hypotheses were formulated and tested. Hypothesis testing showed that costs, size, external pressure and interorganizational trust were significant EDI facilitators, while e-commerce legal framework was a significant EDI inhibitor. The finding that interorganizational trust is significant is a revelation and points to a newer trend of the importance of developing trusting business relationships to mitigate uncertainties in the exchange relationship. t-tests showed that EDI adopters and EDI non-adopters differ significantly in size, top management support, information technology capability, internal championship, external pressure and interorganizational trust variables. The three variables of top management support, external pressure and interorganizational trust were the best differentiators for adoption. Means analysis showed that costs was perceived to be the most important variable while external pressure was perceived to be the least important variable. This study makes practical contribution by providing valuable insights to the company management when considering EDI adoption, to EDI solution vendors when considering how to sell their software and services and to government when formulating technology policies. The theoretical contribution of this study is through extending research work in the area of interorganizational information systems (IOS) by providing better understanding of the research area. This study also updates the information to the body of EDI knowledge of Malaysian manufacturers. Finally, the study has shown the appropriateness of the use of Diffusion of Innovation theory variables and Social Exchange Theory variables in the Tornatzky-Fleischer’s (1990) Technology-Organizational-Environmental framework.